Hubungan problematic online game use dengan pola asuh pada remaja - Sulistyo, Juandika Tri; Evanytha, Evanytha; Vinaya, Vinaya (Konsorsium Psikologi Ilmiah Nusantara, 2015)
Development of entertainment feature over the internet gives some positive and negative impacts for the users. One of the negative outcomes is the over engagement in the excessive use of online games that create psychological, social, school and work difficulties in a person’s life is known as Problematic Online Game Use (POGU). This research aimed to explore the correlation between parenting style and Problematic Online Game Use (POGU). The participants for this research are 200 Indonesian adolescents, ranging from 14 to 24 years old. The term POGU in this research was based on the study conducted by Kim and Kim (2010). An Indonesian version of Problematic Online Game Use Scale and questionnaire to measure parenting style were employed to collect the data. The results of this study indicated that there was a significant relationship between authoritative parenting and POGU, whereas no significant relationship was found between the other three types of parenting, namely: authoritarian, permissive, and neglected to POGU. This study showed higher tendency of Problematic Online Game Use among adolescents with authoritative type of parenting, compared with authoritarian, permissive, and neglected type of parenting.